Effect of Coagulants in Curd forming in Cheese Making - Wardhani, Dyah Hesti; Jos, Bakti; Abdullah, Abdullah; Suherman, Suherman; Cahyono, Heri (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2018)
Cheese is one of the popular dairy products with high nutrient content. Coagulation as an important process in making cheese, wherein, the curd will be separated from the milk whey. This coagulation can use the enzyme rennet, acid, or a combination of both. This study aims to study the effect of coagulant agents on yield, protease enzyme activity, and curd texture on cheese making. Coagulant agents used are acetic acid, citric acid, lime and lemon combined with the enzyme rennet. The process begins with pasteurized milk and analyzed, the milk is pasteurized and analyzed first to obtain moisture content, density and pH. The coagulant added is 25-45% with a base of 50 ml of milk and 5 mL of the enzyme rennet. The curd formed is then separated from the whey using a filter cloth and analyzed for its water content and pH. The coagulant of acetic acid and citric acid produced a higher yield curd of 94.66% (4% acetic acid) and 93.9% (5% citric acid) compared to the highest yield of curd that can be produced by lime and lemon coagulant which is 68 72% (lemon orange 45%) and 61.84% (lime 45%). The texture of the curd formed by lime and lemon juice is more fragile than the curd texture with coagulant of acetic acid and citric acid. Each coagulant provides a diverse response to protease enzyme activity.